Attention and Recall of Point-of-sale Tobacco Marketing: A Mobile Eye-Tracking Pilot Study - Maansi Bansal-Travers; Sarah E. Adkison; Richard J. O'Connor; James F. Thrasher (AIMS Press, 2016)
Introduction: As tobacco advertising restrictions have increased, the retail 'power wall' behind the counter is increasingly invaluable for marketing tobacco products. Objective: The primary objectives of this pilot study were 3-fold: (1) evaluate the attention paid/fixations on the area behind the cash register where tobacco advertising is concentrated and tobacco products are displayed in a real-world setting, (2) evaluate the duration (dwell-time) of these fixations, and (3) evaluate the recall of advertising displayed on the tobacco power wall. Methods: Data from 13 Smokers (S) and 12 Susceptible or non-daily Smokers (SS) aged 180-30 from a mobile eye-tracking study. Mobile-eye tracking technology records the orientation (fixation) and duration (dwell-time) of visual attention. Participants were randomized to one of three purchase tasks at a convenience store: Candy bar Only (CO; N = 10), Candy bar + Specified cigarette Brand (CSB; N = 6), and Candy bar + cigarette Brand of their Choice (CBC; N = 9). A post-session survey evaluated recall of tobacco marketing. Key outcomes were fixations and dwell-time on the cigarette displays at the point-of-sale. Results: Participants spent a median time of 44 seconds during the standardized time evaluated and nearly three-quarters (72%) fixated on the power wall during their purchase, regardless of smoking status (S: 77%, SS: 67%) or purchase task (CO: 44%, CSB: 71%, CBC: 100%). In the post session survey, nearly all participants (96%) indicated they noticed a cigarette brand and 64% were able to describe a specific part of the tobacco wall or recall a promotional offer. Conclusions: Consumers are exposed to point-of-sale tobacco marketing, regardless of smoking status. FDA should consider regulations that limit exposure to point-of-sale tobacco marketing among consumers.